2022
DOI: 10.1186/s12968-022-00894-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of right atrial strain derived from cardiovascular magnetic resonance in non-ischemic dilated cardiomyopathy

Abstract: Background The value of right atrial (RA) function in cardiovascular diseases is currently limited. This study was to explore the prognostic value of RA strain derived from fast long axis method by cardiovascular magnetic resonance (CMR) in patients with non-ischemic dilated cardiomyopathy (DCM). Methods We prospectively enrolled patients with DCM who underwent CMR from June 2012 to March 2019 and 120 age- and sex-matched healthy subjects. Fast lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In accordance with several previous studies based on STE or the fast long-axis method ( 18 , 24 ), we demonstrated that the RA reservoir, conduit, and booster pump function were all impaired in DCM patients, as evidenced by the decreased magnitudes of RA εs, εe, εa, SRs, SRe, and SRa. The mechanism of RA dysfunction in patients with DCM has not been fully elucidated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with several previous studies based on STE or the fast long-axis method ( 18 , 24 ), we demonstrated that the RA reservoir, conduit, and booster pump function were all impaired in DCM patients, as evidenced by the decreased magnitudes of RA εs, εe, εa, SRs, SRe, and SRa. The mechanism of RA dysfunction in patients with DCM has not been fully elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, cardiovascular magnetic resonance-feature tracking (CMR-FT), a novel technique based on routine balanced steady-state free precession (SSFP) cine sequences, offers higher spatial resolution, better reproducibility, and improved definition of endocardial borders, making it increasingly attractive for evaluating RA phasic functions ( 17 ). Moreover, a very recent study using a fast long-axis method found that RA strain was closely associated with poor outcomes in patients with DCM ( 18 ). Nonetheless, studies focused on RA deformation using CMR-FT in DCM patients are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Furthermore, RA structural and functional remodelling are reported risk predictors in several studies. 28,29 The RA also plays an important role in modulating the interactions between the performance of the other heart chambers. Therefore, in patients with AL cardiac amyloidosis, the RA is affected by both direct amyloid deposition and the other chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that RA structural and functional remodelling are prevalent in patients with heart failure (HF), pulmonary arterial hypertension, and hypertrophic cardiomyopathy 25–27 . Furthermore, RA structural and functional remodelling are reported risk predictors in several studies 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the RA function assessed by either 2DSTE as RA strain or 3DE as RA EmF is reduced in DCM compared to that of the control group despite normal RA Vmax values. RA structure and function by CMR are impaired in patients with DCM, and the RA reservoir and conduit strain were demonstrated to be independently associated with adverse clinical outcomes and to have a higher predictive value compared to RA EmF [ 24 ]. However, these findings were demonstrated on Chinese patients, and geographical variations have been found in both RA size and function [ 25 ].…”
Section: Discussionmentioning
confidence: 99%